2018
DOI: 10.1186/s13046-018-0781-8
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of FGF15/19 signaling promotes hepatocellular carcinoma in the background of fatty liver

Abstract: BackgroundUpregulated fibroblast growth factor 19 (FGF19) expression in human hepatocellular carcinoma (HCC) specimens is associated with tumor progression and poor prognosis. Nonalcoholic steatohepatitis (NASH) patients are at high risk for malignant transformation into HCC.MethodsA steatohepatitis-HCC model was established in male C57L/J mice treated with N-nitrosodiethylamine (DEN) and high-fat diet (HFD). A mouse HCC cell line (Hepa1–6) and a mouse hepatocyte line (FL83B) were used to elucidate the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 52 publications
(54 reference statements)
2
53
0
Order By: Relevance
“…Mechanically, it has been discovered that FGF19 increases the phosphorylation of GSK‐3β, resulting in the inactivation of GSK‐3β, and thus leading to the accumulation and activation of β‐catenin . Increasing evidence has shown that FGF19‐mediated Wnt/GSK‐3β/β‐catenin signalling contributes to the promotion of cell proliferation during tumour progression . Therefore, we speculated that FGF19 might regulate keratinocyte proliferation through Wnt/β‐catenin signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically, it has been discovered that FGF19 increases the phosphorylation of GSK‐3β, resulting in the inactivation of GSK‐3β, and thus leading to the accumulation and activation of β‐catenin . Increasing evidence has shown that FGF19‐mediated Wnt/GSK‐3β/β‐catenin signalling contributes to the promotion of cell proliferation during tumour progression . Therefore, we speculated that FGF19 might regulate keratinocyte proliferation through Wnt/β‐catenin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…14 Increasing evidence has shown that FGF19-mediated Wnt/GSK-3β/β-catenin signalling contributes to the promotion of cell proliferation during tumour progression. [30][31][32] Therefore, we speculated that FGF19 might regulate keratinocyte proliferation through Wnt/β-catenin signalling. As expected, we found that FGF19 overexpression increased the phosphorylation of 19,20,33,34 In addition, the Wnt signalling inhibitor Dickkopf-1 is decreased in psoriatic lesional skin.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of FXR by BA triggers the secretion of FGF15/ FGF19 in humans (39), and the beneficial effects of FGF expression on the obese metabolic profile has been well characterized (40). However, the clinical use of FGF has been debated due to the potential for increasing liver tumor development (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is known to be associated with tumor aggressiveness and poor survival, and Zhao et al found that FGF19 induces EMT via the FGFR4/GSK3β/β-catenin axis in HCC cells [34]. In addition, Cui et al reported that FGF15 binds to FGFR4 and promotes the development of HCC by activating EMT and Wnt/β-catenin signaling in a microenvironment in which lipid metabolism is disordered [35].…”
Section: Mechanisms Of the Effects Of Fgf19 On Glucose Metabolism Andmentioning
confidence: 99%